Development of a low background pulsed generator of intermediate energy range neutrons for remote detection of fissile materials - Chornyi, V.; Frolov, A.; Tsepilov, G.; Dubina, V.; Chornyi, A.; Solovyov, V. (Вопросы атомной науки и техники, 2004)
A structure of radiation shielding for a low background pulsed generator of intermediate energy range neutrons was developed on the basis of calculations and the data obtained in the model experiments, and limit parameters for remote detection of fissile materials using this generator were determined and are presented in this paper. The magnetically insulated diode structure and the radiation shielding geometry were optimized in accordance with the performed calculations. У даній роботі представлено конструкцію радіаційного захисту для низькофонового імпульсного генератора проміжних енергій, розробленого на основі комп'ютерних розрахунків і даних модельних експериментів, а також приведені граничні параметри дистанційного виявлення подільчих матеріалів за допомогою цього генератора. Конструкція магнітно-ізольованого діода і геометрія радіаційного захисту були оптимізовані відповідно до проведених обчислень. В данной статье представлено описание конструкции радиационной защиты для низкофонового импульсного генератора промежуточных энергий, разработанного на основе компьютерных вычислений и данных модельных экспериментов, а также приведены предельные параметры дистанционного обнаружения делящихся материалов с использованием этого генератора. Конструкция магнитно-изолированного диода и геометрия радиационной защиты были оптимизированы в соответствии с проведенными вычислениями.